2020
DOI: 10.1183/23120541.00030-2019
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of loss to follow-up of tuberculosis cases under the DOTS programme in Namibia

Abstract: BackgroundIn Namibia, one out of every 25 cases of tuberculosis (TB) is “lost to follow-up” (LTFU). This has impacted negatively on national efforts to end the disease by 2035. The aim of this study was to determine the trends and predictors of LTFU under the directly observed treatment short-course (DOTS) programme in Namibia.MethodsThe study involved a retrospective longitudinal analysis of a nationwide cohort of TB cases registered under the DOTS programme in Namibia from 2006 to 2015. The trends and predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
6
0
2
Order By: Relevance
“…The DOTS strategy was among the three (Stop TB and End TB) scaled-up essential strategies recommended by World Health Organization (WHO) to interrupt TB transmission and the period of infectiousness [12,13]. While the DOTS strategy has been globally adopted, TB patients still end up with poor treatment outcomes [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The DOTS strategy was among the three (Stop TB and End TB) scaled-up essential strategies recommended by World Health Organization (WHO) to interrupt TB transmission and the period of infectiousness [12,13]. While the DOTS strategy has been globally adopted, TB patients still end up with poor treatment outcomes [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 , 20 Fortunately, with the adjustment of treatment strategies in recent years, there are declining trends in loss to follow up (LTFU) and increasing trends in the success rate of TB treatment. 21 , 22 Kibuule et al reported that since the expansion of facility-based DOTS programme to community-based DOTS programme in Namibia in 2005, 23 the mean annual treatment success rate increased by approximately 20% when comparing the pre-intervention (1996–2005) and the post-intervention (2005–2015) periods.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Thus, it is not surprising that limited utility of quality PIS data remains an important bottleneck to healthcare delivery in these settings in public healthcare. 18,19 Previously, the authors have described challenges with quality and utility of PIS data and indicators, as well as misalignment of PIS indicators with National Standard Treatment Guidelines (NSTGs) for Namibia implemented in 2011. [20][21][22] The utility of PIS data among focal persons at public health facilities in Namibia was estimated at 60.7% (target >80%).…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 Thus, it is not surprising that limited utility of quality PIS data remains an important bottleneck to healthcare delivery in these settings in public healthcare. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%